Leading Inclusive Growth: Comparing Business Models in The Coffee Value Chain, West Java Province - Mulyati, Heti; Indrawan, Dikky; Abdullah, Asaduddin; Yusri, Doni (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Smallholders play a critical role in the coffee value chain within West Java Province, with the majority of coffee production originating from their plantations. However, the initiative and involvement of coffee farmers in the value chain remain limited. Consequently, it is imperative to implement an inclusive business model that ensures the participation of all stakeholders.Purposes: This study examines the diversity of inclusive business models in West Java‘s coffee value chains, focusing on collectors in Pangalengan and Lembang, coffee shops with roasteries in Bogor, and farmers’ cooperatives in Garut.Design/Methodology/Approach: Using value chain mapping, business model canvas analysis, and semi-structured interviews with key stakeholders, it explores how these lead firms integrate smallholder farmers into their business models while balancing profit and social impact. The analysis revealed distinct inclusivity approaches across the models, underscoring the significance of adapting strategies to specific regional contexts.Findings/Result: The collector model in Pangalengan and Lembang prioritizes efficiency and market access but may overlook the nuanced needs of farmers. Conversely, the Bogor coffee shop and roastery model fosters direct farmer relationships, promoting quality and shared decision-making. The cooperative in Garut emphasizes collective action and farmer empowerment, although it faces challenges related to governance and market access.Conclusion: This study identifies the key factors for successful inclusive business practices in coffee value chains. Enhancing coffee value chain inclusivity requires robust stakeholder engagement, particularly with smallholders, empowering training, knowledge sharing, and rigorous monitoring and evaluation.Originality/Value/state of the art: These insights include the need for context-specific business models, external actor collaboration, a holistic value-creation perspective, and continuous learning and adaptation. Keywords: business models canvas, coffee value chain, inclusive business, West Java Province, value chain mapping